Religious rhetoric and American politics: the endurance of civil religion in electoral campaigns - Chapp, Christopher B. (Cornell Univ. Press, 2012)
"Examines the role of religious political rhetoric in American elections by analyzing both how political elites use religious language, and how voters respond to different expressions of religion in the public sphere"--Publisher's Web site